Purgatory [videorecording (DVD)] - Dawson, Gordon; Shepard, Sam, 1943-2017; Roberts, Eric, 1956-; Stormare, Peter; Rowe, Brad, 1970-; Wahlberg, Donnie, 1969-; Souther, J. D.; Heinle, Amelia, 1973-; Fiedel, Brad (TNT original, 2005)
Wild Bill Hickock, Doc Holiday, Jesse James, Billy the Kid and more deceased greats of the untamed West get a last chance to undo their violent pasts in a mysterious town that's West of the Pecos and south of Eternity.